Morphological and Prognostic Values of Skin Lesions in Patients with COVID-19 - Mahmoud A. Rageh; Ibrahim H. E. Yousef; Yaser Hosny Ali Elewa; Mofreh Mansour; Omar AbdelHady Omar Ahmed; Sameh Fawzy Fahmy; Ahmad Saeed Aladl; Mohamed Amer; Emad El Rewiny; Manar Elsayed Sallam; Amr Mohammad Ammar; Salma S. Mohammed; et al. (Hindawi Limited, 2024)
The dermatological manifestations of the coronavirus cause severe acute respiratory syndrome. The current study investigates the morphological and histopathological relationship between the emergence of skin lesions and the severity of COVID-19 across the course of the disease via a cross-sectional study. There were skin lesions (maculopapular rash, vesiculobullous lesions, urticarial lesions, cutaneous thromboembolic "CT," and erythema multiforme-like lesions "EM-like") in confirmed COVID-19 instances. A total of 150 patients of both sexes were evaluated morphologically and were classified as early (44% of the total) or late based on the emergence of respiratory symptoms (one week before or two weeks after, respectively). The early and late diagnostic groups represented 44% and 56% of the total patients, respectively. Patients with no skin lesion and one skin lesion showed a significant correlation with disease timeline early and late stages (X2 = 22.38, P<0.001; X2 = 4.432, P<0.001, respectively). CT and EM-like were correlated with the disease severity, X2 = 50.51, P<0.001; X2 = 19.186, P≤0.001, respectively. In conclusion, our data suggested that the onset of dermatological lesions that developed during the COVID-19 pandemic may be a useful diagnostic and prognostic tool for COVID-19 severity. Therefore, a thorough examination of the skin may save time and bring physicians to an accurate diagnosis and, as a result, prompt treatment.